Serum angiostatin levels in diabetic patients with heart failure taking oral antidiabetic therapy or basal insulin and its clinical significance - Birol Yildiz; Ismail Erturk; Galip Buyukturan; Bilgin Bahadir Basgoz; Ramazan Acar; Kenan Saglam (Medicine Science, 2020)
Diabetes mellitus is a metabolic disorder with an increasing incidence all over the world leading to high sequelae and high mortality rates behind other microvascular and macrovascular complications. The deterioration in angiogenesis in particular is known to cause deterioration of vascular complications of diabetes. After the discovery of a natural angiogenesis inhibitor, angiostatin in the ethiopathogenesis of retinopathy and nephropathy, which are frequent complications of diabetes, several successful clinical trials have been made. However, the most lethal complication of diabetes, diabetic heart failure, lacks any trial about effectiveness of angiostatin. In this study, the levels and the clinical significance of angiostatin were investigated in oral antidiabetic or Insulin treated diabetic patients with heart failure. The patient group consisted of 31 patients with a diagnosis of diabetes mellitus and heart failure and the control group included 30 patients with heart failure without diabetes mellitus. Serum levels of angiostatin were studied. A total of 61 subjects were enrolled in the study. The patient group consisted of 31 patients; between the age of 56-88 (73.06 ± 8.7) years, of which 16 (51.6%) were female and 15 (48.4%) were male. The control group included 30 patients; 15 (% 50) women and 15 (50%) of were male, between the ages of 57 to 85 (74.23 ± 8.27). In the case group, the average angiostatin levels were 133.25 ± 78.46 and in the control group it was found to be 121.7 ± 71.81. The average angiostatin levels were similar in diabetic and non-diabetic heart failure groups (p=0.55). The average serum angiostatin levels showed a significant negative correlation with the level of fasting blood glucose. In our study, diabetic patients with heart failure, when compared with non-diabetic patients with heart failure, showed no significant difference in the levels of angiostatin. Levels of angiostatin are not affected by the level of HbA1c. Fasting blood glucose level has a negative correlation with the level of angiostatin. In order to be used in determining the prognosis in diabetic patients with heart failure, further studies are needed on angiostatin levels. [Med-Science 2020; 9(1.000): 45-8]